2003
DOI: 10.1177/0963662503124005
|View full text |Cite
|
Sign up to set email alerts
|

Lay Experts and the Politics of Breast Implants

Abstract: This paper discusses the controversy around breast implants in the United States and Europe. It focuses on the emergence of consumer and support groups for women and offers an analysis of the role they have played in recent policy developments in UK and Europe. The politics of breast implants is seen as a politics of knowledge in which scientific expertise has consistently been deployed in ways that minimize the credibility and legitimacy of women's accounts of their bodies and illness experiences. These women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…This trend is in line with the "layification" of speaking time in the programs. This layification of the speaking time might be explained by the transformation in the patient-doctor relationship that occurred between 1961 and 2000, and the rise of patient activist groups and activism around specific diseases like AIDS (Epstein, 1996) or controversies about treatments (Kent, 2003) or medicine (Andsager and Smiley, 1998). Those contextual developments cannot be derived from this content analysis, although an increase in speaking time for patient groups or representatives of activists was not found in this study.…”
Section: Conclusion and Discussionmentioning
confidence: 68%
“…This trend is in line with the "layification" of speaking time in the programs. This layification of the speaking time might be explained by the transformation in the patient-doctor relationship that occurred between 1961 and 2000, and the rise of patient activist groups and activism around specific diseases like AIDS (Epstein, 1996) or controversies about treatments (Kent, 2003) or medicine (Andsager and Smiley, 1998). Those contextual developments cannot be derived from this content analysis, although an increase in speaking time for patient groups or representatives of activists was not found in this study.…”
Section: Conclusion and Discussionmentioning
confidence: 68%
“…Yet in this and other cases of public opposition, it has been shown that alternative and legitimate citizen framings are routinely dismissed in favour of the technocratic preference of decision-makers, or that to make a case at all, critics need to adopt the language and argumentative form of science (e.g. Darier et al, 1999;Enticott, 2003;Epstein, 1995;Harvey, 2005;Kent, 2003;Robins, 2001;Roth et al, 2003;Wynne, 1982). 1 In response, Wynne develops a position that is critical of 'science's de facto role in modern society as assumed agent of the meaning of public issues ' (2003, p. 410) and Wynne and others (e.g.…”
Section: Scientismmentioning
confidence: 99%
“…Unlike many philosophers of social science, I do not think that these properties signal a fundamental division between the natural and human sciences. It is clear that some social science disciplines are more profoundly shaped by reflexive overlaps than others, while on the other hand many natural science topics involve important experiential, political and ethical contributions and contestations (e.g Kent, 2003;Moore and Stilgoe, 2009;Spence et al, 2011)…”
mentioning
confidence: 99%